2001
DOI: 10.1007/s100480100122
|View full text |Cite
|
Sign up to set email alerts
|

APOE and APOC1 genetic polymorphisms in age-associated memory impairment

Abstract: We studied the distribution of two genetic polymorphisms (APOE and APOC1) in a sample of 100 subjects fulfilling the NIMH criteria for age-associated memory impairment (AAMI) and 124 controls. We found significant associations both for APOE and APOC1 loci and their combinations with the AAMI condition. The findings in our sample suggest that memory-impaired subjects as described by the NIMH may be genetically differentiated from normally aging subjects in relation to these two polymorphisms and indicate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In contrast, whether this allele is also a risk factor for conversion from HC to some form of CIND has been controversial. Some studies have identified an ε4–MCI link (Henderson et al, 1995; Traykov et al, 2002; Zill et al, 2001) and others have not (Bartrés-Faz et al, 2001; Collie, Maruff, & Currie, 2002; Devanand et al, 2005; Heun et al, 2010), which has prompted reviewers to conclude that available data are mixed and inconsistent (Small et al, 2004). However, when salient sources of Type I and Type II error in earlier studies were minimized, using Wave A data from the ADAMS, a clear pattern emerged (Brainerd et al, 2011): Epsilon 4 frequency was elevated in ADAMS MCI participants, relative to HC, VSCI, or AOCI participants, and consistent with many prior studies, ε4 was elevated in AD participants.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, whether this allele is also a risk factor for conversion from HC to some form of CIND has been controversial. Some studies have identified an ε4–MCI link (Henderson et al, 1995; Traykov et al, 2002; Zill et al, 2001) and others have not (Bartrés-Faz et al, 2001; Collie, Maruff, & Currie, 2002; Devanand et al, 2005; Heun et al, 2010), which has prompted reviewers to conclude that available data are mixed and inconsistent (Small et al, 2004). However, when salient sources of Type I and Type II error in earlier studies were minimized, using Wave A data from the ADAMS, a clear pattern emerged (Brainerd et al, 2011): Epsilon 4 frequency was elevated in ADAMS MCI participants, relative to HC, VSCI, or AOCI participants, and consistent with many prior studies, ε4 was elevated in AD participants.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using some of the just-mentioned pre-AD diagnostic categories, ε4 was found to be more common in impaired than in healthy older adults in the following studies: Henderson et al (1995) ;Traykov et al (2002), and Zill et al (2001). In contrast, that result was not obtained in studies by Bartre ´s-Faz et al (2001); Collie, Maruff, and Currie (2002); Devanand et al (2005), and Heun et al (2010). In a review of research on the cognitive effects of ε4, Small, Rosnick, Fratiglioni, and Backman (2004) concluded that the evidence is mixed and inconclusive when it comes to a potential link between ε4 and cognitive impairment that is not accompanied by dementia.…”
mentioning
confidence: 97%
“…Rs56131196 and rs157582 have been reported in GWAS studies on AD and aging-related verbal memory respectively [23, 24], thus lending validation and confidence to our analytic procedure and results. Previous studies suggested that the elderly carrying APOC1 gene tended to perform worse in cognitive scores and showed more severe hippocampal abnormalities [25, 26]. Besides, the APOC1 -knock-out mice might have worse memory performance than those carrying APOC1 [27].…”
Section: Discussionmentioning
confidence: 99%
“…As for mechanism, ApoC1 (apolipoprotein C1) encoded by APOC1 is a member of the apolipoprotein family, which may be involved in multiple biological processes comprising cholesterol metabolism and neuronal apoptosis [28]. But the specific mechanisms by which APOC1 gene modulates the risk of cognitive impairment remain controversial, although some research has been done in this field [26, 29, 30]. The protein that TOMM40 encodes, TOM40 (translocase of the outer mitochondrial membrane 40), constitutes an external mitochondrial membrane channel that promotes the transport of many aggregating proteins to mitochondria [31, 32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation